Peran Pengelolaan SDM dalam Mendukung Penyusunan Laporan Keuangan di BKAD Kota Palangka Raya - Kezia Cleo Evanggelina Lumeno; Achmad Syamsudin; Muhammad Akbar Aditya Saputra; Melany Putri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study analyzes the role of human resource management in supporting the preparation of financial reports at the Regional Finance and Asset Agency (BKAD) of Palangka Raya City. The study focuses on competency development, employee placement, performance appraisal, work coordination, and work environment support in relation to the qualitative characteristics of government financial reports under Government Accounting Standards. This research uses a descriptive qualitative approach with a case study design. Primary data were obtained through in-depth interviews with informants from the accounting division and the general and personnel sub-division. The findings show that the preparation of financial reports depends not only on regulations and systems, but also on employees who are careful, honest, productive, understand rules, and follow work procedures. Competency development through technical guidance, socialization, assistance, reconciliation, and coordination supports employees in completing their tasks. Appropriate placement, E-Kinerja-based appraisal, clear task distribution, leadership support, and adequate facilities also strengthen financial reporting. However, multiple positions, excessive workloads, limited understanding, low accuracy, leadership pressure, and unsuitable training schedules remain obstacles that need continuous improvement.